2015
DOI: 10.1039/c4tc01601g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical co-deposition of sol–gel/carbon nanotube composite thin films for antireflection and non-linear optics

Abstract: Sol-gel/carbon nanotubes (CNTs) nano-composite films were electrochemically deposited by applying negative potential to a conducting substrate, i.e. indium tin oxide (ITO) and Ag grid printed on polyethylene terephthalate (PET). The deposition is driven by the local pH rise on the cathode that catalyzes the formation of sol-gel films. The latter serves as binder and entrapment for CNTs. The 10 deposition can be well manipulated by deposition potential and time, and the film can be selectively electrodeposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…• Firstly, it offers the advantage of depositing layers of uniform thickness over the whole surface of non-flat supports (such as metal or carbon nanofibers [162][163][164], streaked metal surfaces [133,165], ordered macroporous metals [156,166]) or micro-and nanoscale objects (carbon nanotubes [167]), the electrode geometry and size having some impact on film formation and properties [168]. It can cover selectively specific portions of heterogeneous supports, either via electrodeposition only onto the conducting portions of the support (printed circuit, gold mesh, silver grid printed on polyethylene terephthalate) [169,170] or by taking advantage of different overpotentials for the generation of OH − catalyst (Pt nanoparticles on carbon or Pt-Au bimetallic macroporous electrodes), enabling selective sol-gel electro-assisted deposition onto Pt [166,171], whereas the films obtained by dip-coating covered the whole surface of the Pt/C or Pt/Au supports. Of related interest is the formation of free-standing porous silica microstructures by exploiting adhesion differences of the deposit on hydrophilic and hydrophobic surfaces, via the selective removal of silica from the more hydrophobic areas of the substrate (thiol-modified Au) while keeping those firmly attached to the hydrophilic ones (indium-tin oxide) [172].…”
Section: The Concept Of Electrochemically Assisted Deposition Of Sol-...mentioning
confidence: 99%
See 2 more Smart Citations
“…• Firstly, it offers the advantage of depositing layers of uniform thickness over the whole surface of non-flat supports (such as metal or carbon nanofibers [162][163][164], streaked metal surfaces [133,165], ordered macroporous metals [156,166]) or micro-and nanoscale objects (carbon nanotubes [167]), the electrode geometry and size having some impact on film formation and properties [168]. It can cover selectively specific portions of heterogeneous supports, either via electrodeposition only onto the conducting portions of the support (printed circuit, gold mesh, silver grid printed on polyethylene terephthalate) [169,170] or by taking advantage of different overpotentials for the generation of OH − catalyst (Pt nanoparticles on carbon or Pt-Au bimetallic macroporous electrodes), enabling selective sol-gel electro-assisted deposition onto Pt [166,171], whereas the films obtained by dip-coating covered the whole surface of the Pt/C or Pt/Au supports. Of related interest is the formation of free-standing porous silica microstructures by exploiting adhesion differences of the deposit on hydrophilic and hydrophobic surfaces, via the selective removal of silica from the more hydrophobic areas of the substrate (thiol-modified Au) while keeping those firmly attached to the hydrophilic ones (indium-tin oxide) [172].…”
Section: The Concept Of Electrochemically Assisted Deposition Of Sol-...mentioning
confidence: 99%
“…• Fourthly, nano-object can be physically entrapped within sol-gel films in the course of their electrochemically induced growth, offering a way to immobilize durably some particles that are somewhat difficult to accommodate onto electrode surfaces in a mechanically stable form. Examples are available for clays [189,190], metal or metal oxide nanoparticles [191][192][193], carbon nanomaterials [167,170,194,195], giving rise to composite films applicable in various fields (sensing, electrocatalysis, protective coatings). An interesting approach is the controlled growth of sol-gel matrices with different thickness and functional groups as nanoparticle imprinted thin films on electrodes that are likely to recognize and detect selectively gold nanoparticles based on their dimensions [196].…”
Section: The Concept Of Electrochemically Assisted Deposition Of Sol-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, electrodeposition can be carried out at moderate potential, room temperature and in aqueous solutions. For example, we have shown that a variety of nanomaterials, such as latex nanoparticles [19], WO 3 nanorods [20], graphene [21] and carbon nanotubes [22] could be electrodeposited successfully following this approach. In most cases, the applied electrical potential caused the oxidation or reduction of water, which changed the pH on the electrode surface and eliminated the net surface charge of the dispersed nanomaterials causing them to aggregates and deposit irreversibly on the electrode surface.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we have demonstrated the direct deposition of nanomaterials from their dispersions using electrochemistry [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%